Բիոէթիկայի աշխարհայացքային առանձնահատկությունները - Սուսաննա Դավթյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматривается аксиологический аспект биоэтических проблем. In the given article the axiological aspect of the bioethical problems are discussed.
Keywords: Philosophy